Marriage and Conjugal Sex: Paul’s “Marriage Debt” and Kant’s “Conjugal Rights” - Calano, Mark Joseph T. (Archīum Ateneo, 2016)
The Code of Canon Law states that sex is a requisite for the consummation of a marriage but that the conjugal act must be performed in a “human way.” Divided into three parts, this paper investigates the place of hum an sex in a consummated marriage by looking into the Pauline understanding of the “marriage debt” found in 1 Corinthians 7 and the Kantian notion of “conjugal rights.” The first part is an exegesis of Paul’s texts suggesting that a couple are obligated by a certain debt to provide for the sexual gratification of their partners. The second part discusses implications of t he Kantian principle of humanity in marriage and sexual activity. For Kant, marriage is a contract that includes the exchange of rights of access to the body. By explicating Paul’s and Kant’s understanding of the relationship between marriage and sex, the paper provides a better understanding of the place and r ole of human sex in a consummated marriage.